The Legal Aspects of Corruption in Sport = Prawne aspekty korupcji w sporcie - Paweł Szwajdler (Kazimierz Wielki University, 2016)
Szwajdler Paweł. The Legal Aspects of Corruption in Sport = Prawne aspekty korupcji w sporcie. Journal of Education, Health and Sport. 2016;6(5):445-451. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62001 http://ojs.ukw.edu.pl/index.php/johs/article/view/3852     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.     The Legal Aspects of Corruption in Sport Prawne aspekty korupcji w sporcie   Paweł Szwajdler e-mail: pawel.szwajdler@onet.pl   Nicolaus Copernicus University in Torun, Poland     Abstrakt: W niniejszym artykule przedstawiono zarys obowiązujących oraz proponowanych rozwiązań jurydycznych, przeciwdziałających zjawisku korupcji w sporcie. Na początku rozważań poruszono  zagadnienia o charakterze ogólnym, a mianowicie zdefiniowano pojęcie korupcji oraz pokazano jej oddziaływanie na funkcjonowanie społeczeństwa. Następnie omówiono wpływ zachowań korupcyjnych na życie sportowe. W głównej części pracy  zaprezentowano wybrane rozwiązania skierowane przeciwko korupcji w sporcie oraz postulaty dotyczące przedmiotowego zagadnienia, wskazywane przez przedstawicieli doktryny prawa sportowego.         Abstract: The author of this paper presents legal measures against corruption in sport. The overall issues such as the notion of corruption and influence of corruption on the society are discussed in the beginning of this article. Furthermore, it is showed the influence of corruptive behaviours on sport. In the main part of this paper, the author considers selected measures against corruption in sport and opinions of legal researchers about them.         Key words: sport, corruption, law, anti- corruption measures, integrity of sport Słowa kluczowe: sport, korupcja, prawo, przeciwdziałanie korupcji, integralność sportu